ANALYSIS OF ERODIBILITY AND SLAKING CHARACTERISTICS OF TOPSOIL (SURFACE SOIL) AND OVERBURDEN ROCK OF COAL MINE DUMP - Demmy Wenanda, Kadek
Overburden is material that lies on the surface and has no economic value. Overburden consists of topsoil and cover rock. Topsoil is the topmost layer of soil that is soft, easy to dig and rich in humus, while cover rock is a layer of rock that is very hard and difficult to dig. Topsoil still plays an important role in supporting the success of reclamation or revegetation activities in former mining areas, because topsoil has a level of softness and humus as a good planting medium. While cover rock has a relatively larger grain size and a strong and solid structure that is certainly not good as a planting medium when compared to topsoil. Erodibility is the level of sensitivity or resistance of a material to being easily or not eroded (Sartohadi, 2013). Each material has different erodibility depending on the structure that can be seen from the aggregate stability of a material. This aggregate stability can be seen through slake durability testing. By knowing the erodibility and slaking index, it is possible to estimate the potential of the cover rock to have a level of fluidity like topsoil. Samples were divided into 3 types, namely topsoil, cover rock 1 (OB1) and cover rock 2 (OB2) which were carried out in duplicate. The results show that topsoil has the highest erodibility of 0.36 while cover rock 1 (OB1) is 0.31 and cover rock 2 (OB2) is 0.27. Topsoil has a relatively high slaking rate compared to cover rock 1 and cover rock 2, namely the average slaking rate of topsoil is 14.7 x10-7 g/cm2/s while cover rock 1 is 6.1 x10-7 g/cm2/s and cover rock 2 is 4.23 x10-7 g/cm2/s. To increase the slaking rate can be done by reducing the size of the cover rock so as to accelerate the process of soil formation such as topsoil.